At a glance about mindfulness - Abdullah, Nasiha (Fakulti Pengurusan Perniagaan, UiTM Terengganu, 2021)
Mindfulness simply means being aware. Nothing else. Nothing less will suffice. Being fully present and conscious of your actions, thoughts, and emotions. Mindfulness may appear overly simple, but with practice, it can help you calm your nerves, see challenges in a new light, tap into your creativity, and improve your stress response.